1994
DOI: 10.2113/gsecongeo.89.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Origin of placer gold nuggets and history of formation of glacial gold placers, Gold Creek, Granite County, Montana

Abstract: Placer gold along the upper portions of Gold Creek, near Deer Lodge, Montana, occurs in Pliocene(?) fossil alluvial placers, Pleistocene till, and alluvium. The upper Gold Creek placers yielded an estimated 175 to 200 kg gold during 1890 to 1990. The gold probably originated in veins, skarn, or replacement deposits in Paleozoic and Mesozoic sedimentary units near the contact with Late Cretaceous granodiorite of the Royal stock. Gold was initially concentrated in alluvial placers along the ancestral Gold Creek … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 16 publications
4
19
0
1
Order By: Relevance
“…A similar conclusion was drawn by Loen (1993), who stated that the supergene alteration of placer gold grains from Montana was confined to the formation of gold-rich rims. Thus, it is concluded that with regards to the present study area, the particle size of the gold grains reflects the original grain size in the hypogene ore, and that processes leading to the development of authigenic gold in the alluvial environment are either absent or insignificant.…”
Section: Evidence For Authigenic Goldsupporting
confidence: 77%
See 1 more Smart Citation
“…A similar conclusion was drawn by Loen (1993), who stated that the supergene alteration of placer gold grains from Montana was confined to the formation of gold-rich rims. Thus, it is concluded that with regards to the present study area, the particle size of the gold grains reflects the original grain size in the hypogene ore, and that processes leading to the development of authigenic gold in the alluvial environment are either absent or insignificant.…”
Section: Evidence For Authigenic Goldsupporting
confidence: 77%
“…Several workers have investigated the effect of distance of transport on the characteristics of alluvial gold particles, both in morphological and chemical terms, (Hallbauer and Utter, 1977;Groen et al, 1990;Herail et al, 1990;Loen, 1993Loen, , 1995Knight et al, 1999a). Whereas there is a consensus that morphological features are related to distance travelled, the relationship between transport and chemical change is less clear.…”
Section: The Effect Of Transport Of Gold Grainsmentioning
confidence: 99%
“…There is also no evidence for gold grains which are entirely authigenic in the Klondike District, Yukon Territory (Chapman et al, ). Studies of gold from Britain and Ireland (Chapman et al, ), North America (Knight, Mortensen, & Morison, ; Lange & Gignoux, ; Loen, ), and New Zealand (Youngson & Craw, ) failed to find any evidence for augmentation of the alluvial population by authigenic processes, and the internal characteristics of the gold grains were considered consistent with those from the hypogene source. These results give a strong indication that, for alluvial gold in temperate climates, the contribution of authigenic gold is negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Territory (Chapman et al, 2002). Studies of gold from Britain and Ireland (Chapman et al, 2000), North America (Knight, Mortensen, & Morison, 1999;Lange & Gignoux, 1999;Loen, 1994), and New…”
Section: Microchemistry and Gold Source Typementioning
confidence: 99%
“…The study of the morphology and composition of gold grains from stream sediments, soils and regolith has been widely used as a tool in gold exploration programmes (Hallbauer & Utter, 1977;Averill & Zimmerman, 1986;Grant et al 1991;Styles, 1995). According to Loen (1994), the placer gold occurs as coarse-sized, oval to elongated grains characterized by rounded protuberances and inclusions of quartz and sulphide minerals. Native gold is a very malleable mineral and, in a supergenic natural environment, grains are highly deformed during transport.…”
Section: Introductionmentioning
confidence: 99%